Nest comb bee density of the dwarf honey bee species Apis florea F. and Apis andreniformis Smith (Hymenoptera: Apidae) - Bajaree Chuttong (2018)
© 2018 MPH. Two species of dwarf honey bees; Apis florea F. and A. andreniformis Smith were studied to examine their nest comb bee density. Ten colonies of each species were obtained in 2017 and 2018 from the Mae Rim district, Chiang Mai province in northern Thailand at elevations ranging from 600 to 1,000 m. The average number of adult workers of A. florea and A. andreniformis were 9,169 ± 6,499 and 5,081 ± 2,520, while the numbers of drones were 142 ± 112 and 73 ± 30 respectively. The comb areas were determined using the software program ImageJ. The average comb area of the sampled A. florea colonies is, like the adult bee population, double that of A. andreniformis. The bee density statistic (A. florea, 13.1 vs A. andreniformis, 14.4 adults/cm2) is comparable between the two species. Statistically there is a significant difference between the species when comparing adult bee populations (P≤0.05) and comb area (P≤0.01). There is no significant difference concerning the density, bees/cm2, between the two species.